Dampak Penyalahgunaan Narkotika Terhadap Perceraian di Kabupaten Langkat (Studi Putusan Pengadilan Agama No. 1512/Pdt.G/2022/Pa.Stb) - Putri Rahayu (Journal Smart Law, 2024)
This research aims to find out the impact of narcotics abuse on divorce, especially in Langkat Regency. This type of research is Library Research, where this research is studied using library data in the form of books as the source. The method used in this research is a qualitative method, which emphasizes the quality and descriptive understanding of the decision. The author's approach is to use a juridical-normative approach by looking at legal objects related to laws. The legal materials used are primary legal materials and secondary legal materials. The management of legal materials is carried out in a deductive manner, namely drawing conclusions from a general problem to the concrete problems faced. The results of the research show that the main causes of divorce in the Stabat Religious Court are continuous disputes and quarrels that cannot be resolved amicably and the lack of harmony between husband and wife which is triggered by the influence of narcotics abuse which has an impact on the attitude, behavior and actions of a husband towards wife, children and family. This causes divorce.